Large magnetocaloric effect in gadolinium borotungstate Gd3BWO9. Issue 34 (6th August 2020) - Yang, Ziyu; Zhang, Huihui; Bai, Mingjun; Li, Wei; Huang, Shaolong; Ruan, Shuangchen; Zeng, Yu-Jia
Abstract : A potential solid-state magnetic cooling candidate Gd3 BWO9 is proposed, which shows an exceptionally large magnetocaloric effect. Abstract : Herein, we report a potential solid-state magnetic cooling candidate gadolinium borotungstate Gd3 BWO9 that shows an exceptionally large magnetocaloric effect. Experimental investigations on the crystal structure, bulk magnetic and heat capacity properties down to 300 mK were performed, along with the theoretical analysis of the electronic and magnetic features through density functional theory (DFT) and mean-field approach. The isothermal magnetic entropy change was identified to be 454 mJ K −1 cc −1 for a field variation of 9 T at 2.4 K, which are among the highest records ever reported. The substantial magnetocaloric effect makes Gd3 BWO9 a strong alternative for cryogenic refrigeration at ultra-low temperatures and in the magnetic gas liquefaction.